2022
DOI: 10.1186/s13223-022-00679-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding attitudes and obstacles to vaccination against COVID-19 in patients with primary immunodeficiency

Abstract: Background Patients with primary immunodeficiency (PID) are at increased risk for infections such as SARS-CoV-2 (COVID-19), due to the nature of their diseases and being immunocompromised. At this time, four vaccines against COVID-19 (Pfizer-BioNtech’s Comirnaty®, Moderna’s Spikevax®, AstraZeneca’s Vaxzevria®, Johnson & Johnson’s Janssen®) have been approved for use by Health Canada. Due to the novelty of these vaccines, clinical studies in patients with PID are ongoing. Despite limited evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 21 publications
6
15
1
Order By: Relevance
“…Our data on vaccine hesitancy also agrees with the Canadian study results that reported the primary reason for vaccine hesitancy was uncertainty of the benefits ( 26 ). However, other studies reported safety concerns among patients with IEI or AIIRDs.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our data on vaccine hesitancy also agrees with the Canadian study results that reported the primary reason for vaccine hesitancy was uncertainty of the benefits ( 26 ). However, other studies reported safety concerns among patients with IEI or AIIRDs.…”
Section: Discussionsupporting
confidence: 90%
“…However, pharmacist-physician coaching (42) might be ineffective among patients with ultrarare and rare diseases since they generally seek professional advice from a specialist before receiving any vaccines. Our data on vaccine hesitancy also agrees with the Canadian study results that reported the primary reason for vaccine hesitancy was uncertainty of the benefits (26). However, other studies reported safety concerns among patients with IEI or AIIRDs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations